2020
DOI: 10.1002/ldr.3757
|View full text |Cite
|
Sign up to set email alerts
|

Forest conversion alters the structure and functional processes of tropical forest soil microbial communities

Abstract: Many studies have been carried‐out on the effects of forest conversion on soil microbial community composition and diversity. However, impacts on soil microbial functions and how diversity changes across scales are poorly understood. To fill the research gap, we used metagenomic sequencing and 16S rRNA and ITS gene sequences to evaluate the microbial composition, diversity, and function of 260 soil samples collected from tropical rainforest and rubber plantation sites across Hainan Island, South China. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…They integrated the results of 1235 global change factors of eight ecosystems including agricultural land, tundra, temperate forests, tropical and subtropical forests, Mediterranean vegetation, grasslands, deserts and wetlands, and concluded that soil pH is the most important factor that can be used to predict the impact of global change factors on microbial alpha diversity [27]. In particular, the results are also consistent with the results of Flores-Rentería et al [66] and Lan et al [46]. The composition of soil microorganisms in tropical rainforests is related to soil pH.…”
Section: Soil Ph Effects On Rhizosphere Soil Microbes In the Soil Env...supporting
confidence: 66%
See 2 more Smart Citations
“…They integrated the results of 1235 global change factors of eight ecosystems including agricultural land, tundra, temperate forests, tropical and subtropical forests, Mediterranean vegetation, grasslands, deserts and wetlands, and concluded that soil pH is the most important factor that can be used to predict the impact of global change factors on microbial alpha diversity [27]. In particular, the results are also consistent with the results of Flores-Rentería et al [66] and Lan et al [46]. The composition of soil microorganisms in tropical rainforests is related to soil pH.…”
Section: Soil Ph Effects On Rhizosphere Soil Microbes In the Soil Env...supporting
confidence: 66%
“…The soil fungal communities in tropical forests in Puerto Rico are mainly Ascomycota and Basidiomycota [51]. Similarly, Lan et al [46] found that Ascomycota and Basidiomycota are the major phyla of soil fungi communities in Hainan Island. Therefore, the results of this study indicate that the microbial composition of the rhizosphere soil of high-altitude tropical forests is similar to that of low-altitude tropical forests.…”
Section: Diversity Of Rhizosphere Microbial Communitymentioning
confidence: 94%
See 1 more Smart Citation
“…The annual expanding rates of monoculture plantations have increased to 2% over the past 25 years (FAO, 2015). Most conversion from natural forests to plantations has occurred in subtropical regions (Lan et al, 2021) . Such conversion results in alterations of ecosystem services and functions along with changes in plant diversity and soil nutrients loss (Krashevska, Klarner, Widyastuti, Maraun, & Scheu, 2015;Yang, Zhu, Xu, & Zheng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of clear-cutting for the environment are, among others, unfavourable growth conditions for species requiring shelter when they are young, the threat of wind and water erosion to the surface, especially in the mountain areas, the risk of secondary swamping in wetlands, drying of the topsoil layers, and a strong expansion of herbaceous vegetation (Borelli et al, 2017;Ussiri & Johnson, 2007). According to many authors, changes in forest cover can alter microbial community and accelerate the degree of organic matter decomposition, leading to C losses (Ishikawa et al, 2007;Jamroz et al, 2014;Lan et al, 2020;Prescott, 2005;Smolander et al, 2019;Ussiri & Johnson, 2007;Valenzuela & Cervantes, 2021).…”
Section: Introductionmentioning
confidence: 99%